Cutaneous Carcinosarcoma: a Clinicopathologic and Immunohistochemical Analysis of 11 Korean Cases - Kwak, Hyun-Bin (J Korean Med Sci, 2018)
BACKGROUND: Cutaneous carcinosarcoma is a rare biphasic tumor comprising malignant epithelial and heterologous mesenchymal elements. Data on the clinical and histopathologic characteristics of this tumor in Asian populations are not available. The purpose of this study was to investigate the clinicopathologic and immunohistochemical features of cutaneous carcinosarcoma in the Korean population. METHODS: We retrospectively reviewed the records of 11 patients with cutaneous carcinosarcoma who were diagnosed from 2006 to 2016. RESULTS: The mean patient age at diagnosis was 71.5 years (range, 43–96 years) and there was a men predilection. The most common site of cutaneous carcinosarcoma was the head and neck (8/11, 72.7%). Histopathologically, most tumors showed a characteristic morphology consisting of two types of tumor cells, varied differentiated epithelial cells (such as basal or squamous cells) and spindle cells with transition zones between the two components. These two cell types also demonstrated variable immunohistochemical characteristics. CONCLUSION: Although the number of cases in this study was limited, our results provide valuable insight into the clinical and histopathologic characteristics of cutaneous carcinosarcoma in the Korean population.